A healing promoting wound dressing with tailor-made antibacterial potency employing piezocatalytic processes in multi-functional nanocomposites. Issue 7 (8th February 2022) - Zhang, Yi; An, Qi; Zhang, Shuting; Ma, Zequn; Hu, Xiantong; Feng, Mengchun; Zhang, Yihe; Zhao, Yantao
Abstract : An anti-bacterial patch, which is achieved by mounting polypyrrole/carbon nanotube catalysts on a piezoelectric–dielectric film is developed. Abstract : Developing a novel antibiotics-free antibacterial strategy is essential for minimizing bacterial resistance. Materials that not only kill bacteria but also promote tissue healing are especially challenging to achieve. Inspired by chemical conversion processes in living organisms, we develop a piezoelectrically active antibacterial device that converts ambient O2 and H2 O to ROS by piezocatalytic processes. The device is achieved by mounting nanoscopic polypyrrole/carbon nanotube catalyst multilayers onto piezoelectric–dielectric films. Under stimuli by a hand-held massage device, the sterilizing rates for S. aureus and E. coli reach 84.11% and 94.85% after 10 minutes of operation, respectively. The antibacterial substrate at the same time preserves and releases drugs and presents negligible cytotoxicity. Animal experiments demonstrate that daily treatment for 10 minutes using the device effectively accelerates the healing of infected wounds on the backs of mice, promoting hair follicle generation and collagen deposition. We believe that this report provides a novel design approach for antibacterial strategies in medical treatment.